Causal abductive reasoning in discourse processing: Evidence from eyetracking - Solstad, Torgrim; Bott, Oliver (Proceedings of the Amsterdam Colloquium, 2024)
Psycholinguistic research has provided abundant evidence that both the nature of a causal relation as well as world knowledge have an immediate influence on the processing of explanatory discourse (e.g., Canestrelli, Mak, and Sanders 2013; Köhne-Fuetterer et al. 2021; Xiang and Kuperberg 2015). However, little is known about which particular reasoning processes are immediately triggered as we integrate new information. The present study provides first evidence that two types of abductive reasoning (Aliseda 2006) can be observed during processing, involving partial explanations that would either contradict world knowledge (abductive anomaly) or not be predicted by such knowledge (abductive novelty). In an experiment applying eyetracking during reading we identified two distinct processing signatures for the two types of abduction.